Water, floods, water disasters: a dialogue open to various disciplines (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The paper will show the difficulties of scholars in reconstructing the reality of past centuries (15th-18th), often filtered by what is lived in the present. Until the 19th century, freshwaters were a living and ever‐changing world, with basic resources for the communities (commons). Subsequently this world has gradually disappeared and so its memory. In the appendix is presented an initiative, based on volunteering, which will help to understand some aspects of the unexpected changes that have occurred over the past centuries.
Keywords: Historical perception; environment; landscape changes and transformations; commons; data collection